Model Analisis Pengaruh Aktiva dan Hutang Terhadap Kinerja Keuangan Dengan Laba sebagai Variabel Moderasi pada Perusahaan Sub Sektor Food And Baverages di Bursa Efek Indonesia Periode 2016-2020 - Yunan Surono; Ali Akbar; R Adisetiawan (Universitas Batanghari Jambi, 2022)
Financial performance is an analysis conducted to see the extent to which a company has implemented by using financial implementation rules properly and correctly. This study aims to explore and prove the effect of asset and debt variables on the company's financial performance with the profit variable as a factor that strengthens or weakens the relationship between these variables. The independent variables in this study are assets and debt as independent variables with financial performance as the dependent variable and profit as a moderating variable. The performance of listed companies in the food and beverage sub-sector which has a large and significant difference and fluctuated during the study period. This research uses SEM (Structural Equation Modeling) analysis based on component or variance, namely Partial Least Square (PLS). The results of the study show 1) The asset variable has no effect on the financial performance variable in the food and beverage sub-sector companies on the Indonesia Stock Exchange for the period 2016 - 2020. 2) The debt variable has no effect on the financial performance variable. 3) The profit variable is able to moderate the relationship between the asset variable and the financial performance variable and has a positive direction (strengthening) its influence on financial performance. This moderating variable can be classified into predictor moderation where the profit variable has an effect on the financial performance variable, while the moderating effect 1 has no effect on the financial performance variable. 4) The profit variable is able to moderate the relationship between the debt variable and the financial performance variable and has a positive direction (strengthening) its influence on financial performance. This moderating variable can be classified into predictor moderation where the profit variable has an effect on the financial performance variable, while the moderation effect 2 has no effect on the financial performance variable.